Ambivalence in environmental representation: A theoretical contribution (Sociologisk Forskning, 2019)
In this paper, we examine the phenomenon of representation through the theoretical lens of ambivalence, concentrating on the people involved in representation: representatives . We argue that the theoretical concept of ambivalence can be helpful in analysing and understanding the various tensions environmental and other representatives encounter in their practice . Based on the concepts of “sociological ambivalence”, “ideological dilemma”, and “the organizational centaur”, as well as on insights from social studies of science and sustainability studies, the paper develops a typology of three potential sources of ambivalence: role conflicts, value conflicts, and conflicts between goals and means . In addition, the paper identifies various ways of co- ping with ambivalence, including the construction of meta-norms, organizational and network support, pragmatism, drawing boundaries for reasonable and acceptable actions, rule bending and discursive negotiation . The paper concludes that the concept of ambivalence adds crucial insights to the positions, practices, and challenges of environmental representatives and notes that ambivalence is not only a matter of tensions and conflicts but can be a source of reflexivity, learning, and agency.
Keywords: representatives, coping, environment, organization, dilemma, sustainability, uncer- tainty, tension